Pharmacologic immunosuppression of mononuclear phagocyte phagocytosis by caffeine. Issue 6 (25th October 2015) - Steck, Ryan P.; Hill, Spencer L.; Weagel, Evita G.; Scott Weber, K.; Robison, Richard A.; O'Neill, Kim L.
Abstract: Caffeine is the most widely used neurostimulant in the world. There is considerable debate on its effect on immune cells as it has been shown to antagonize adenosine receptors (ARs), which mediate an anti‐inflammatory switch in activated immune cells. A second target is phosphodiesterase, where it acts as an inhibitor. If the primary effect of caffeine on mononuclear phagocytes were to antagonize ARs we would expect cells exposed to caffeine to have a prolonged proinflammatory response. The aim of this study was to investigate the effects and mechanism of action of caffeine in mononuclear phagocytes. Human mononuclear phagocytes were separated from whole blood and pretreated with protein kinase A inhibitor (PKA) and then exposed to micromolar physiological concentrations of caffeine. Phagocytosis and phagocytosis exhaustion were quantified using flow cytometry. Treatments were analyzed and compared to controls, using a beta regression controlling for factors of age, gender, caffeine intake, and exercise. We found that caffeine suppresses phagocytosis at micromolar physiological concentrations. This suppression was prevented when mononuclear phagocytes were pretreated with PKA inhibitor, suggesting that caffeine's phagocytic suppression may be due to its function as a phosphodiesterase inhibitor, pushing cells towards an anti‐inflammatory response. Additionally, these effects are altered by regular caffeine intake and fitness level, emphasizing that tolerance and immune robustness are important factors in mononuclear phagocyte activation. These results demonstrate that caffeine may be acting as a phosphodiesterase inhibitor and suppressing phagocytosis in mononuclear phagocytes by promoting an anti‐inflammatory response.